2019
DOI: 10.1371/journal.pone.0218441
|View full text |Cite
|
Sign up to set email alerts
|

Route of inoculation influences Trypanosoma congolense and Trypanosoma brucei brucei virulence in Swiss white mice

Abstract: Experiments on infections caused by trypanosomes are widely performed in Swiss white mice through various inoculation routes. To better understand the effect of route of trypanosome inoculation on disease outcomes in this model, we characterised the virulence of two isolates, Trypanosoma bruce i KETRI 2710 and T . congolense KETRI 2765 in Swiss white mice. For each of the isolates, five routes of parasite inoculation, namely intraperitoneal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…The prepatent period of 5 to 6 days for intraperitoneal inoculation of T brucei brucei and T congolense in our study compares well with experimental infections in mice in which the mean prepatent period was 3.8 days for T brucei brucei and 6.5 days for T congolense . 22 Also, in our study, T brucei brucei produced higher level (4.0 × 10 7 trypanosomes/mL of blood) and more fluctuating peaks of parasitaemia than T congolense (1.3 × 10 6 trypanosomes/mL of blood). The understanding of trypanotolerance includes the ability of the tolerant breeds to control parasitaemia.…”
Section: Discussionsupporting
confidence: 61%
“…The prepatent period of 5 to 6 days for intraperitoneal inoculation of T brucei brucei and T congolense in our study compares well with experimental infections in mice in which the mean prepatent period was 3.8 days for T brucei brucei and 6.5 days for T congolense . 22 Also, in our study, T brucei brucei produced higher level (4.0 × 10 7 trypanosomes/mL of blood) and more fluctuating peaks of parasitaemia than T congolense (1.3 × 10 6 trypanosomes/mL of blood). The understanding of trypanotolerance includes the ability of the tolerant breeds to control parasitaemia.…”
Section: Discussionsupporting
confidence: 61%
“…routes ( Table 1). However, a small number of comparative experiments have revealed that inoculation routes can substantially affect outcome (43,44). For example, it has been shown that the percentage of BALB/c mice with detectable parasitemia after infection by T. brucei differed between animals infected i.p.…”
Section: Influence Of the Infection Route For Trypanosome Disseminationmentioning
confidence: 99%
“…infected mice in a dose-dependent manner (43). Moreover, the impact of infection route on infectivity also differs between trypanosome species (44). For example, T. congolense infected intramuscularly (i.m.)…”
Section: Influence Of the Infection Route For Trypanosome Disseminationmentioning
confidence: 99%
See 2 more Smart Citations